Pemanfaatan Google Form Sebagai Sarana Layanan Dan Pengaduan Masyarakat Pondok Rangon, Jakarta Timur - Selli Mariko; Ek Ajeng Rahmi Pinahayu; Aulia Ar Rakhman Awaludin; Luh Putu Widya Adnyani; Sriyono Sriyono; Nani Mulyani (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
Partners for PKM (Community Service) activities are community groups from RT.03 Pondok Rangon, East Jakarta. There are several problems faced by partners to be used as a background for implementing PKM activities. As for the various problems, they include: 1. Many urban people who live in the RT.003 area do not update their data to the local RT head; 2. Service delays and public complaints due to invalid data; 3. Incomplete complaint and service files; 4. There are other activities of public stakeholders that make them not in place. Therefore, the PKM team offers a solution that forms the basis of the goal to overcome the problems of PKM partners. The main objective of PKM activities is to utilize information technology (google form) to support services and complaints from RT residents. 009 Pondok Rangon Village, Cipayung, East Jakarta. The method for implementing PKM activities is online training with reference to the material developed by the PKM Team. Outcomes from PKM activities are: 1. Research Report; 2. Journal Articles; 3. Appropriate technology for the community in the form of improving soft skills; 4. The service process and public complaints are faster and more efficient by utilizing the Google Form.